Comparative Effectiveness of Epidural Levobupivacaine Analgesia and Fentanyl Elastometric Pump For Postoperative Pain Management at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh - Al-Muqsith, Al-Muqsith (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Postoperative pain management plays a pivotal role in optimizing surgical recovery and minimizing postoperative morbidity. In clinical practice, epidural analgesia and continuous intravenous opioid administration via elastomeric pumps are commonly utilized to control postoperative pain. This study aimed to evaluate and compare the analgesic effectiveness and adverse event profiles of continuous epidural levobupivacaine infusion and fentanyl administration using an elastomeric pump in patients undergoing digestive and gynecological surgery at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh. This analytic comparative observational study included adult postoperative patients who received either epidural levobupivacaine or intravenous fentanyl via elastomeric pump. Pain intensity was assessed using the Numeric Rating Scale (NRS) at 24 and 48 hours postoperatively. Statistical analysis was conducted using the Mann–Whitney U test. Both analgesic modalities achieved satisfactory postoperative pain control, with no statistically significant differences in NRS scores at 24 hours (p = 0.759) and 48 hours (p = 0.050). Opioid-related adverse effects, including nausea, vomiting, and sedation, were more frequently observed in the fentanyl group, whereas hypotension occurred in a small proportion of patients receiving epidural analgesia. These findings indicate that continuous epidural levobupivacaine and fentanyl elastomeric pump provide comparable effectiveness and safety for postoperative pain management following digestive and gynecological surgery.